A comparative study on the efficacy and safety of intravenous levetiracetam and phenobarbitone in the treatment of neonatal seizures - Bhasin, Deergha; Sethi, Anuj; Chaurasiya, Om Shankar; Chhabra, Kawalpreet (International Journal of Contemporary Pediatrics, 2025)
Background: Seizures are the most common manifestation of neurological insult during the neonatal period with a significant risk of mortality and subsequent neurological disability. Phenobarbitone has been the mainstay of treatment for decades despite its limited efficacy and potential adverse effects. Levetiracetam being a newer antiepileptic with favourable pharmacological and clinical profile and better neurodevelopmental outcomes may be used as an alternative first line antiepileptic. This study compares the efficacy and safety of intravenous levetiracetam and phenobarbitone in the treatment of neonatal seizures. Methods: Prospective randomized controlled trial conducted at level 3 Neonatal Intensive Care Unit including 150 neonates 0-28 days with clinical seizures randomized to receive either intravenous Levetiracetam or Phenobarbitone as first line antiepileptic. Cessation of seizures for 24 hours duration after drug administration is considered as primary outcome measure. Results: Seizure control was noted in 53.3% neonates in phenobarbitone group, which was significantly higher as compared levetiracetam (21.3%, p<0.05) after first loading. A significantly higher percentage of neonates in levetiracetam group required further doses and another drug (25.3%). Adverse effects and requirement of mechanical ventilation was significantly higher in patients of phenobarbitone group (22.7%) (p<0.05). However neurological outcomes measured by HINE score did not show significant difference between the groups(p>0.05). Conclusions: Phenobarbitone is found to be more efficacious than levetiracetam as a first line antiepileptic in terms of seizure control while levetiracetam requires more frequent dosing but with better safety profile and survival rates. Thus, levetiracetam can be considered as an alternative in treatment of neonatal seizures.